Effect of Grinding Operation on Product Morphology in Stirred Mills - Roufaill, Reem; Klein, B.; Blaskovich, R. (CMP, 2011)
Morphology is a tool that is rarely used for mineral breakage mechanism evaluation. Ground particles are typically assessed for their size distribution. They are also visually analyzed using image analysis. However, image analysis is not a comprehensive evaluation of the particle surface texture. It evaluates particle’s size parameters such as area, diameter, and perimeter amongst other features. On the other hand, morphology analysis takes the particle assessment to another level of detail. Morphology analysis evaluates particles’ roundness, elongation and angularity that would indicate the degree of roughness of the particle. According to Roufail and Klein (2009), rougher surfaces are generated due to breakage along grain boundaries – inter-granular breakage. Mill operation, particularly mill speed, dictates the dynamics in the mill. Stirred mills are known to break the particles via abrasion under standard operation. However, if the dynamics of the grinding media in the mill are changed, the particles could be more exposed to impact and compression loading that would lead to a different mode of breakage. In this paper, the effect of material properties and mill operating conditions on particle morphology will be studied. Hard non-sulfide versus soft sulfide minerals are compared, namely quartz and galena, respectively. Extreme mill speeds are tested covering the range of 1000 to 2000 rpm for a 4-litre Netzsch (ISA) mill. In addition to particle size distribution, micro-analysis is executed in the form of morphological analysis using a tested manual roughness point counting technique.